Peran Guru Pendidikan Agama Islam dalam Membina Sikap Keagamaan Pada Peserta Didik - Lili Yulyanti; Sukman Sukman (IAIN Sorong, 2017)
This study aims to study the role of Islamic Religious Education teachers in fostering the religious attitudes of class XI students at SMA GUPPI Salawati, and the driving and inhibiting factors for Islamic Religious Education Teachers in fostering religious attitudes in class XI students. Special talks were held by Islamic Religious Education teachers at Salawati GUPPI High School Against grade XI students. This research uses qualitative research. qualitative research using descriptivemethods. This research is based on primary data (primary) and secondary data (supporting). The main data (primary) includes observations, interviews, and documentation. While the secondarydata (supporting) is the data obtained from the library. The results of this study indicate that Islamic Religious Education teachers at GUPPI Salawati High School have actively supported andcan prove quite good in conducting religious attitudes towards class XI students. This can be seen from the education provided by Educating Religion to students, Give good examples, Give Motivation to children, Invite students to participate in religious activities, Train students tosupport each other, support each other, support parents, teachers and friends, given advice and direction, supervising students, guiding, discussing, and evaluating. With these roles, there is a change in the attitude of good religion in class XI students of SMA GUPPI Salawati. Then to achieve a goal there must be certain obstacles, impulses or motivations that will hinder and encourage. The driving forces are Facilities, Teachers, Parents, Schools and Environments which are a barrier to the family environment, the surrounding environment is less favorable than lazy friends, and technology is like a cellphone by playing games.